Regorafenib alone or in combination with high/low-dose radiotherapy plus toripalimab as third-line treatment in patients with metastatic colorectal cancer: protocol for a prospective, randomized, controlled phase II clinical trial (SLOT) - Zhou, Shujuan; Wang, Chenchen; Shen, Lijun; Wang, Yan; Zhang, Hui; Wu, Ruiyan; Wang, Yaqi; Chen, Yajie; Xuan, Yan; Xia, Fan; Zhang, Zhen; Wan, Juefeng (Frontiers in Oncology, 2023)
Combination strategies to improve immunotherapy response in microsatellite stable metastatic colorectal cancer (MSS mCRC) remain an unmet need. Several singlearm clinical trials have shown promising synergistic effects between regorafenib and ICIs; however, some contradictory results have also been reported. Randomized controlled trials are needed to further validate the combination of regorafenib with ICIs.then continue regorafenib and toripalimab treatment. The primary endpoint is the objective response rate, and the secondary endpoints are disease control rate, duration of remission, median progress-free survival, median overall survival, and adverse events. Recruitment started in August 2023 and is ongoing.https://clinicaltrials.gov/study/NCT05963490?cond=NCT05963490&rank=1, identifier NCT05963490, registered on July 19th, 2023.